Production of cold "Kinutil" (Philippine eggnog) using carabao's milk from the Philippine Carabao Center and nipa (Nypa fruticans Wurmb.) Vodka - Pascual, Mitchel Olive M. (2011)
Alcoholic beverage is one of the products considered to be a universal drug. Studies have shown that moderate intake of these product provides health benefits such as reduce cardiovascular problems. This study was done to develop an indigenous drink "kinutil" with a twist since it is meant to be served as cold. The main component of the cold "kinutil" was condensed milk form Philippine Carabao Center's Carabao's milk. The raw milk was characterized in order to standardize the sweetened condensed milk. The raw milk contained 21.48% total solids, 10.49% fat, 11.02% solid non-fat, a pH of 6.8 and it contains 0.175% Lactic acid. The sweetened condensed milk that was prepared from the raw milk has 42.5% total milk solids and 42% sugar. "Kinutil" with varying levels of condensed milk was produced: 45%, 55% and 65%. A microbiological study on the effectiveness of the employed pasteurization process was done in order to ensure the product's safety against, Salmonella spp. After ensuring that the formulations wee safe for consumption, sensory evaluation was done to find the most preferred product. Preference ranking test was used to determine which of the formulations was most preferred and Basker's table was used to analyze the responses. The formulation with 45% sweetened condensed milk was most preferred and was chosen as the final product. Acceptability testing was done in order to analyze for specific attributes. The data gathered was analyzed using Sign test. From the analysis it was found out that all the attributes namely, appearance, flavor, viscosity, aftertaste, alcoholic aroma and overall acceptability were considered to be acceptable. The final product is slightly acidic with a pH of6.4 and a toatl soluble solid of 27.6